A efetividade das garantias processuais penais e o discurso de combate à corrupção - Andorfato, João Jacinto Anhê (2018)
The recent corruption scandals exposed a old problem. In an emergency agenda, a punitive movement emerges that does not only occupy the discourses of lay Brazilians, but also mobilizes our police, judicial and public prosecutorial authorities, who are moved by public opinion to draw up new strategies and new measures to combat the problem. Corruption in no way should be tolerated and must be harshly repressed by society and by the agencies of criminal prosecution. Notwithstandng, combating corruption or any other crime, however serious it may be the offense and its social consequences, does not justify the distortion of criminal procedural guarantees that historically are the foundation of control and limitation in face of the punitive power of the State. Society must ensure that it is able to discern the excesses of the state's punitive power and the institutions that exercise it in order to avoid the emergence of pathologies such as criminal and procedural law of exception in which moral values are enough to support the criminal sciences: the good becomes a criminal value, the truth a procedural value and the justice a legal value. The desire for punitiveness sometimes obfuscates the necessary precautions to legitimize the interventions of the organs of criminal prosecution, which, in view of the current political crisis, makes it essential to analyze the idea of Justice from the perspective of criminal procedural lessons, placing in poles of contraposition the criminal procedural guarantees and the anti-corruption discourse